Development and validation of signature peptide-based isotope dilution liquid chromatography-mass spectrometry for bovine lactoferrin purity assessment - Yan, Jingjing; Yang, Mengrui; Wang, Min; Han, Yiyi; Zhou, Jian; Ma, Yingqing; Wang, Tongtong; Li, Liang (Microchemical journal, 2025)
[Display omitted] •Signature peptide-based ID-LC-MS/MS for quantification of bovine lactoferrin was reported.•The two-stage IDMS that included the quantification of the synthetic peptide by AA-based IDMS and certification of bovine lactoferrin by signature peptide-based IDMS is fully SI-traceable.•The proposed method detected natural and denatured lactoferrin in infant formulas while the HPLC standard method only detected active lactoferrin. A bovine lactoferrin (bLF) quantification method using signature peptide-based IDMS that is fully traceable to SI is presented. The two stages IDMS method's two stages include quantifying the synthetic peptide by AA-based IDMS via acid hydrolysis and the bLF certification by signature peptide-based IDMS via enzyme digestion. The purity of signature peptide was assessed to be 96.7 % with an uncertainty of 1.95 %, and the bLF was determined to be 0.941 ± 0.024 g/g. The specificity, linearity, and uncertainty are assessed. The quantitative result of the present method is consistent with previous mass balance method (0.938 ± 0.011 g/g) and AA-based IDMS (0.937 ± 0.027 g/g) results. The LOD and LOQ were 35 ug/g and 117 ug/g, respectively, and the uncertainties resulting from the analysis processes are evaluated. Furthermore, we determined bLF in infant formulas using the developed IDMS method and standard HPLC method, and their quantitative results bias is due to the measurement of active concentration and total concentration (ratio of 25 % to 49 %). The proposed method can benefit the development of relevant matrix certified reference materials.